Peran Orang Tua dalam Mencegah Pergaulan Bebas Anaknya Desa Sudimoro Kecamatan Tulangan Kabupaten Sidoarjo - Yohana Ervina Widyanti; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2023)
The purpose of this study was to describe the role of parents in preventing their children's promiscuity in Sudimoro Village, Tulangan District, Sidoarjo Regency. The focus in this study is the actions and words that parents take when carrying out their functions in order to prevent the involvement or opportunities for their children to be involved in promiscuity. The promiscuity of teenagers is meant by teenagers who have had sexual relations outside of marriage or free sex, drug abuse, and drinking. The theoretical basis used is Biddle & Thomas's role theory which consists of several indicators, namely expectations, norms, forms of behavior, assessments and sanctions. This research uses qualitative research with descriptive research design. The informants of this study were six parents who had teenage children aged 13 to 15 years and were not involved in promiscuity. One of the parents in this study worked (father worked while mother did not work). Data collection techniques in this study were in-depth interviews and observation. The data validity technique used triangulation technique. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of parental research in preventing their children's promiscuity and for children's awareness and personal responsibility by laying the foundation of religion as the main education for children in preventing promiscuity, utilizing children's free time with activities to develop talents and interests, applying time limits outside the home as a form of supervision and controlling children's associations and explaining the dangers of promiscuity as self-help for children. It's just that in explaining the dangers of promiscuity there is a difference that girls are more reminded of the dangers of free sex while boys are reminded not to fall into promiscuity such as free sex, drug abuse, and drinking. Keywords: Role, parents, adolescent promiscuity.